Формула Неванлинны для усеченной матричной тригонометрической проблемы моментов - Загороднюк, С.М. (Український математичний журнал, 2012)
Ця робота є продовженням дослiдження зрiзаної матричної тригонометричної проблеми моментiв, розпочатого ав- тором (див. Укр. мат. журн. – 2011. – 63, № 6. – С. 786 – 797). У данiй роботi одержано формулу Неванлiнни для цiєї проблеми моментiв у загальному випадку. При цьому припускається, що задано бiльш нiж один момент, проблема моментiв розв’язна i має бiльш нiж один розв’язок. Коефiцiєнти вiдповiдного матричного дробово-лiнiйного перетворення явно виражено через заданi моменти. Наведено простi умови визначеностi проблеми моментiв. The paper continues the investigation of the truncated matrix trigonometric moment problem originated by the author in Ukr. Mat. Zh., 63, No. 6, 786–797 (2011). The Nevanlinna formula for the indicated moment problem is deduced in the general case. It is assumed that there is more than one moment and that the moment problem is solvable and has more than one solution. The coefficients of the corresponding matrix linear fractional transformation are expressed in the explicit form via the given moments. Simple determinacy conditions are presented for the moment problem.